Legal Nature and Inheritance of Virtual Property in Ukraine and the World: Current Status, Problems, Prospects - Давидова, Ірина Віталіївна; Давидова, I. В.; Давыдова, Ирина Виталиевна; Davydova, Iryna V.; Діденко, Лариса Василівна; Діденко, Л. В.; Диденко, Лариса Васильевна; Didenko, Larysa V.; Томіна, Вікторія Юріївна; Томіна, В. Ю.; Томина, Виктория Юриевна; Tomina, Viktoriia Yu. (Hemisferios University, 2021)
In recent years, there has been a growing interest in such a phenomenon as a digital inheritance. Sooner or later, users of social networks or online games begin to think about the status of their virtual assets, as they become valuable since users have spent a lot of time to earn them. However, legislation on digital inheritance remains either imperfect or does not answer the question of what happens to digital property after one’s death. The study aimed to describe the situation in the field of digital inheritance through the concepts of virtual property and IT objects. We used systemic, formal-legal, and hermeneutic methods to describe the state of the art in the area of virtual property and digital inheritance through the lens of jurisprudence. The found results suggest that digital inheritance is a growing problem due to imperfect or absent legislation with simultaneously increasing role and importance of the virtual world and digital assets in everyday life. Accordingly, we have found that court decisions set the tone for the development of the legislative process in this field, but at the moment, we are only at the beginning of the creation of solid and harmonized legislation towards digital inheritance. It is also determined that the concept of virtual property does not contradict the general principles of civil law, so it can be applied in the context of digital inheritance.

В останні роки зростає інтерес до такого явища, як цифрове успадкування. Рано чи пізно користувачі соціальних мереж або онлайн-ігор починають замислюватися про статус своїх віртуальних активів, оскільки вони стають цінними, оскільки користувачі витратили багато часу, щоб їх заробити. Однак законодавство про цифрове успадкування залишається або недосконалим, або не відповідає на питання, що відбувається з цифровою власністю після смерті. Дослідження мало на меті описати ситуацію у сфері цифрового успадкування через поняття віртуальної власності та ІТ-об’єктів. Ми використовували системні, формально-юридичні та герменевтичні методи, щоб описати стан мистецтва у сфері віртуальної власності та цифрового спадкування через призму юриспруденції. Отримані результати свідчать про те, що цифрове успадкування є зростаючою проблемою через недосконалість або відсутність законодавства з одночасним зростанням ролі та значення віртуального світу та цифрових активів у повсякденному житті. Відповідно, ми виявили, що судові рішення задають тон розвитку законодавчого процесу у цій сфері, але на даний момент ми лише на початку створення міцного та гармонізованого законодавства щодо цифрового успадкування. Також визначено, що поняття віртуальної власності не суперечить загальним принципам цивільного законодавства, тому може застосовуватися в контексті цифрового успадкування.
Davydova I. Legal Nature and Inheritance of Virtual Property in Ukraine and the World: Current Status, Problems, Prospects / I. Davydova, L. Didenko, V. Tomina // Ius Humani. Law Journal. - Vol. 10. – Iss. 2. - Hemisferios University, 2021. – P. 1-26.
Keywords: virtual property; IT objects; digital inheritance; social networks; online games; віртуальна власність; IT-об’єкти; цифрове успадкування; соціальні мережі; онлайн-ігри; Research Subject Categories::LAW/JURISPRUDENCE